Risk factors and clinical characteristics of Pneumocystis jirovecii pneumonia in lung cancer - Lee, Eun Hye (Sci Rep, 2019)
Solid malignancies are associated with the development of Pneumocystis jirovecii pneumonia (PJP). This study aimed to evaluate the risk factors for PJP among patients with lung cancer. This retrospective case-control study compared patients who had lung cancer with PJP (n = 112) or without PJP (n = 336) matched according to age, sex, histopathology, and stage. PJP definition was based on (i) positive PCR or direct immunofluorescence results for pneumocystis, (ii) clinical symptoms and radiological abnormalities that were consistent with a pneumonic process, and (iii) received targeted PJP treatment. The development of PJP was associated with radiotherapy (RTx), concurrent chemoradiotherapy (CCRTx), lymphopenia, and prolonged high-dose steroid therapy (20 mg of prednisolone equivalent per day for ≥3 weeks). Multivariate analysis revealed independent associations with prolonged high-dose steroid therapy (odds ratio [OR]: 1.96, 95% confidence interval [CI]: 1.06–3.63; p = 0.032) and CCRTx (OR: 2.09, 95% CI: 1.27–3.43; p = 0.004). Steroid use was frequently related to RTx pneumonitis or esophagitis (29 patients, 43.3%). Prolonged high-dose steroid therapy and CCRTx were risk factors for PJP development among patients with lung cancer. As these patients had a poor prognosis, clinicians should consider PJP prophylaxis for high-risk patients with lung cancer.